T-cell ligands modulate the cytolytic activity of the CD33/CD3 BiTE antibody construct, AMG 330 - Laszlo, G S (Blood Cancer J, 2015)
Preclinical and emerging clinical studies demonstrate that bispecific T-cell engaging (BiTE) antibody constructs can potently lyse targeted tumor cells, but the determinants for their activity remain incompletely understood. Using human acute myeloid leukemia (AML) cell lines engineered to overexpress individual T-cell ligands, we found that expression of the inhibitory ligands, PD-L1 and PD-L2, reduced the cytolytic activity of the BiTE antibody construct targeting CD33, AMG 330; conversely, expression of the activating ligands, CD80 and CD86, augmented the cytotoxic activity of AMG 330. Consistent with these findings, treatment with an activating antibody directed at the co-stimulatory T-cell receptor, CD28, significantly increased AMG 330-induced cytotoxicity in human AML cell lines. Using specimens from 12 patients with newly diagnosed or relapsed/refractory AML, we found that activation of CD28 also increased the activity of AMG 330 in primary human AML cells (P=0.023). Together, our findings indicate that T-cell ligands and co-receptors modulate the anti-tumor activity of the CD33/CD3 BiTE antibody construct, AMG 330. These findings suggest that such ligands/co-receptors could serve as biomarkers of response and that co-treatment strategies with pharmacological modulators of T-cell receptor signaling could be utilized to further enhance the activity of this targeted therapeutic.